Cognitive impairment measured by event-related potentials during early and late postoperative period following intravenous or inhalation anaesthesia - Holečková, Irena; Kletečka, Jakub; Štěpánek, David; Žídek, Slavomír; Bludovský, David; Pouska, Jiří; Mautner, Pavel; Přibáň, Vladimír (Clinical neurophysiology, 2018)
OBJECTIVE: This study investigated modification in cognitive function following inhalation (IA) and total intravenous (TIVA) anaesthesia measured using auditory ERPs (Event Related Potentials). METHODS: Auditory ERPs examination with N1, P3a and P3b component registration was carried out one day before surgery (D-1) and on the first (D+1), sixth (D+6) and 42nd (D+42) days after surgery. Results were compared between two anaesthetic groups. RESULTS: On D+1, N1 latency was increased in the IA group. A significant reduction was observed in amplitude of the P3a component on D+6, which persisted up to D+42 for both IA and TIVA groups. A reduction in the amplitude of P3b on D+1 with normalization by D+6 was found in both groups as well. CONCLUSIONS: Intravenous and inhalation anaesthesia lead to similar changes in cognitive function as determined by ERPs, both during the early and late postoperative periods. It cannot be clearly confirmed whether the observed effects are due to anaesthesia or other unmonitored perioperative factors. SIGNIFICANCE: Post anaesthetic changes represent a subclinical impairment; nevertheless, they represent a potential risk for subsequent development of cognitive difficulties.
Keywords: senioři; inhalační anestezie; Cognitive Dysfunction; evokované potenciály; intraoperační neurofyziologická monitorace; pooperační období; Cognition; Postoperative Period; Evoked Potentials; Middle Aged; mužské pohlaví; Adult; Intraoperative Neurophysiological Monitoring; ženské pohlaví; Anesthesia, Intravenous; Humans; ERPs; intravenózní anestezie; kognitivní dysfunkce; lidé středního věku; Anaesthesia; Anesthesia, Inhalation; dospělí; Female; Aged; P3; lidé; Male; N1